How and when does proactive personality predict career adaptability? A study of the moderated mediation model - Li, Hui; Xu, Ziyue; Song, Suhao; Jin, Hui (Frontiers in Psychology, 2024)
In the present study, we explored the relationship between proactive personality and career adaptability to construct a cross-level moderated mediation model based on conservation of resources (COR) theory. Conducting a time-lagged study involving three data collection points from 587 employees across 104 teams in China, we examined how and when proactive personality predicts employees' career adaptability by strengths use as a mediator as well as managerial coaching as boundary conditions. The results revealed that proactive personality predicted strengths use, which in turn influenced career adaptability, with managerial coaching moderating the indirect relationship between proactive personality and career adaptability through strengths use. Consequently, our findings suggest that in contexts where managerial coaching lacks guidance, facilitation, and inspiration, proactive personality encourages employees to leverage their strengths, subsequently enhancing their career adaptability. Finally, we discussed the theoretical and practical implications of our findings, addressed limitations, and proposed directions for future research.